Christoph Drecoll: Rediscovering the Viennese Worth - Birgit Haase and Adelheid Rasche (Costume : The Journal of the Costume Society, 2019)
The once illustrious name of the German-born couturier Christoph Drecoll (1851–1939) is nowadays almost forgotten. The information referring to his name and fashion house in fashion encyclopaedias as well as on online sites is limited, vague, inaccurate and partially contradictory. Many of the discrepancies derive from the fact that different companies used the name Drecoll at the same time. This situation has led to misinterpretations of the historical circumstances and to incorrect attributions of existing clothing in costume collections. This article outlines the complex story of the life and work of the fashion designer Christoph Drecoll with crucial new findings, resulting from a joint research project in progress. Based on intensive archival and material culture studies in European and American collections, the case study of Christoph Drecoll not only sheds light on his almost forgotten fashion house, but also illustrates basic economic, aesthetic and social principles in the context of the international fashion business around the turn of the twentieth century.
Keywords: Drecoll; fashion; haute couture; costume; fancy dress; Vienna; Paris; Berlin; Belle Époque; fashion business